Partial characterization of different isolates of Xanthomonas albilineans and production of a polyclonal antibody for rapid disease detection. - Dela Cueva Fe M.; Natural, Marina P. (2010)
Seventeen potential isolates of the leaf scald bacterium were isolated from sugarcane leaves collected froM iloilo and Victorias City, Negros Occidental. Pure cultures of each isolate maintained in Modified Wilbrink’s Medium (MWM) slants were inoculated on sugarcane plants, (VMC 97-79) or pathogenicity. Polymerase Chain Reaction (PCR) using specific primers was done to confirm the identity of the bacterium. The cultural and physiological characteristics of the different isolates were determined. All isolates were Gram-negative, and rod-shaped, aerobic, able to grow at 28C, utilized glucose, mannose and glycerol but not arabinose.

Pure culture was used for antiserum production in a 3-month old white rabbit. The 4th bleed was found to yield the highest titer and was considered as the best bleed. The 4th bleed was found to yield the highest titer and was considered as the best bleed. This was obtained one week after the 7th injection. An absorbance reading of 3.165 was obtained when tested against 8 10 CFU ml of bacterial suspension and 1:1000 antiserum dilution. A dilution of the produced polyclonal antiserum to 1:10000 (v/v) in antibody buffer yielded an absorbance reading of 1.283 at 405 nm using a 8 10 dilution of bacterial suspension in carbonate coating buffer.

A 1:1000 dilution of the produced antiserum reacted positively to the 14 yellow bacteria isolated from sugarcane even when diluted at 8 10 CFU ml. Non-sugarcane Xanthomonas spp such as Xanthomonas oryzae pv. Oryzae, Xanthomonas oryzae pv. Oryzae pv.oryzicola and Xanthomonas axonopodis pv. Poinsetticola yielded negative reactions against the antiserum in indirect ELISA.

Indexing of introduced varieties of sugarcane inPost-Entry quarantine Greenhouse, IPB, UPLB showed that 12 out of 170 sugarcane leaf samples, (9 symptomatic and 3 asymptomatic) were positive by ELISA using the developed antibody against Xanthomonas albilineans.
Keywords: Leaf scald; Xanthomonas albilineans